2020
DOI: 10.1002/jcla.23352
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of serum long non‐coding RNA ANRIL with risk factors, functional outcome, and prognosis in atrial fibrillation patients with ischemic stroke

Abstract: Background This study aimed to evaluate the predictive value of long non‐coding RNA (lncRNA) antisense non‐coding RNA in the INK4 locus (ANRIL) for atrial fibrillation (AF) patients with ischemic stroke and investigate its correlation with risk factors, functional outcome, and prognosis. Methods A total of 386 consecutive AF patients were recruited. AF patients were followed up for 24‐48 months by outpatient follow‐up, telephone follow‐up, and medical record. The time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Furthermore, reduced expression of lncRNA ANRIL is observed in AIS patients compared to controls, also it negatively correlates with inflammatory cytokines and disease severity in AIS patients 29 . However, lncRNA ANRIL is increased in atrial fibrillation patients with ischemic stroke compared with atrial fibrillation patients without ischemic stroke, also it positively correlates with the disease severity in atrial fibrillation patients with ischemic stroke 30 . Despite the clinical application of lncRNA ANRIL in cerebrovascular disease, no relevant study investigates its clinical role in neurodegenerative disease including PD patients.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, reduced expression of lncRNA ANRIL is observed in AIS patients compared to controls, also it negatively correlates with inflammatory cytokines and disease severity in AIS patients 29 . However, lncRNA ANRIL is increased in atrial fibrillation patients with ischemic stroke compared with atrial fibrillation patients without ischemic stroke, also it positively correlates with the disease severity in atrial fibrillation patients with ischemic stroke 30 . Despite the clinical application of lncRNA ANRIL in cerebrovascular disease, no relevant study investigates its clinical role in neurodegenerative disease including PD patients.…”
Section: Discussionmentioning
confidence: 94%
“…Two studies analyzed datasets of Gene Expression Omnibus via bioinformatic analysis, respectively, and identified several genes which were involved in AF-related stroke ( 199 , 200 ). In addition, studies have shown that abnormal expression of non-coding RNAs, such as lncRNA ANRIL, hsa-miR-22-3p, was associated with functional outcome or prognosis in AF patients, and could potentially serve as potential biomarkers for AF-related IS ( 201 , 202 ). On the basis of current research, it can be expected that new and promising genetics biomarkers for AF-related IS will be further discovered in the near future.…”
Section: Novel Markers Of Genetics and Bioinformaticsmentioning
confidence: 99%
“…To be able to predict the risk of stroke in AF patients, Zeng et al monitored AF patients and compared the levels of the lncRNA ANRIL (antisense non-coding RNA in the INK4 locus) in the stroke group and a non-stroke group. The results showed that higher lncRNA ANRIL levels often correlate with a greater risk of stroke ( 98 ).…”
Section: Non-coding Rnas In Atrial Fibrillationmentioning
confidence: 99%